Tertiary students’ perceived value of practical work as contributing to the learning of science - Emson, Wendy (Auckland University of Technology, 2013)
This thesis focuses on practical work as pedagogy in the teaching and learning of science. In particular the emphasis is on students’ perceived value of practical work in science courses offered from pre-degree to final year degree level courses at a university in Auckland, New Zealand. It seems a common assumption that the teaching of science will include a practical component. For instance, the School of Applied Sciences at Auckland University of Technology (AUT) offers a significant practical component within almost every course offered. This thesis explores the assumption that practical work should be included in the delivery of science courses. A range of views on the nature of science, the acquiring of knowledge and theories of learning are investigated, as well as the ways in which these may underpin the use of practical work as pedagogy in science education. The research described in this thesis took the form of a case study in which students in a range of science courses at AUT were asked to complete a questionnaire and a small number of respondents were then interviewed. Questionnaires were used to gather a large number of responses across a range of subject areas and a range of levels of study. Interviews were utilised to gather more in-depth responses. The data collated from the questionnaires and interviews was analysed thematically. Perhaps not surprisingly, the findings of this case study indicate overwhelming support by students for practical work. The dominant themes which emerged indicated that practical work not only supports learning and understanding in science, but also provides learning opportunities that classroom learning does not provide. The findings of this thesis would seem to support and justify the continued delivery of practical work in science courses. While the responses did not reveal how students believe practical work supports their learning and understanding, some respondents affirmed the less explicit aims of practical work in science education, such as the development of a sense of inquiry, the ability to problem solve and the ability to think critically. This then leads to the question as to whether practical work, as delivered in Applied Science courses at AUT, provides opportunities to potentially meet all of the aims which are expected and hoped for by students, the researcher and her colleagues. While this thesis establishes that students value highly the practical component in science courses, the need to further investigate the style of delivery of practical work to meet wider aims also emerged from this study.
Keywords: Science education; Practical work